Influence of untreated chronic plastic iridocyclitis on intraocular pressure in leprous patients. Issue 4 (April 1981) - Brandt, F; Malla, O K; Anten, J G
Abstract : The intraocular pressures of a total of 1015 eyes of leprous patients who never had ophthalmological care or local eye treatment were measured. The patients were categorised according to the type of leprosy they had the eyes were categorised as without or with chronic plastic iridocyclitis. In patients with the tuberculoid and lepromatous types of leprosy the intraocular pressure was significantly lower in eyes with chronic plastic iridocyclitis than in unaffected eyes. It has been shown that chronic plastic iridocyclitis which remains untreated for many years results in significantly lower intraocular pressure.